Micropropagation and Comparative Study of Chemical Components of Essential Oils of in-vitro and in-vivo Grown Mentha spicata L. - Paudel, B. R.; Pant, B. (Nepal Journal of Science and Technology, 2007)
Axenic shoot culture of Mentha spicata L. was established from young shoots of the plant naturally growing in the field. Large number of multiple shoots were observed on MS media supplemented with NAA (0.5ppm) and BAP (1ppm) within eight weeks of culture. Extensive root formation was observed on MS medium supplemented with 1 ppm NAA. Essential oils from both in vitro and in vivo samples showed l- carvone as a major constituent, however, the in vitro samples showed higher concentration of menthol than in vivo samples. Nepal Journal of Science and Technology Vol. 7, 2006